Alveolar epithelial cell dysfunction and epithelial-mesenchymal transition in pulmonary fibrosis pathogenesis - Zheng, Caopei; Zhang, Ling; Sun, Yuqing; Ma, Yingmin; Zhang, Yulin (Frontiers in Molecular Biosciences, 2025)
Pulmonary fibrosis (PF) is a progressive and lethal interstitial lung disease characterized by aberrant scar formation and destruction of alveolar architecture. Dysfunctional alveolar epithelial cells (AECs) play a central role in initiating PF, where chronic injury triggers apoptosis and disrupts epithelial homeostasis, leading to epithelial-mesenchymal transition (EMT). This dynamic reprogramming process causes AECs to shed epithelial markers and adopt a mesenchymal phenotype, fueling fibroblast activation and pathological extracellular matrix (ECM) deposition. This review systematically explores the multi-layered mechanisms driving AECs dysfunction and EMT, focusing on core signaling axes such as transforming growth factor-β (TGF-β)/Smad, WNT/β-catenin, NF-κB-BRD4, and nuclear factor erythroid 2-related factor 2 (Nrf2), which regulate EMT and fibroblast-ECM interactions. It also highlights emerging regulators, including metabolic reprogramming, exosomal miRNA trafficking, and immune-epithelial interactions. Furthermore, understanding these mechanisms is essential for developing targeted therapeutic strategies to modulate these pathways and halt or reverse fibrosis progression, offering critical insights into potential clinical treatments for PF.